(untitled) (Texas Journal of Agriculture and Biological Sciences, 2025)
The article presents the results of scientific research conducted on the results of the assessment of the productivity indices of varietal samples in the experimental field of the optional international preliminary trial of durum wheat in the experimental field of the Laboratory of genetics, selection and seed growing of durum wheat. Based on the results of the study, samples of durum wheat with high productivity indicators were selected